A Cluster-based Method to Quantify Individual Heterogeneity in Tuberculosis Transmission. Issue 2 (8th December 2021) - Smith, Jonathan P.; Gandhi, Neel R.; Silk, Benjamin J.; Cohen, Ted; Lopman, Benjamin; Raz, Kala; Winglee, Kathryn; Kammerer, Steve; Benkeser, David; Kramer, Michael R.; Hill, Andrew N.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Recent evidence suggests transmission of Mycobacterium tuberculosis (Mtb) may be characterized by extreme individual heterogeneity in secondary cases (i.e., few cases account for the majority of transmission). Such heterogeneity implies outbreaks are rarer but more extensive and has profound implications in infectious disease control. However, discrete person-to-person transmission events in tuberculosis (TB) are often unobserved, precluding our ability to directly quantify individual heterogeneity in TB epidemiology. Methods: We used a modified negative binomial branching process model to quantify the extent of individual heterogeneity using only observed transmission cluster size distribution data (i.e., the simple sum of all cases in a transmission chain) without knowledge of individual-level transmission events. The negative binomial parameter k quantifies the extent of individual heterogeneity (generally, k < 1 indicates extensive heterogeneity, and as k → ∞ transmission becomes more homogenous). We validated the robustness of the inference procedure considering common limitations affecting cluster size data. Finally, we demonstrate the epidemiologic utility of this method by applying it to aggregate US molecular surveillance data from the US Centers for Disease Control and Prevention. Results: The cluster-based method reliably inferred k using TB transmission cluster data despite a high degree of bias introduced into the model. We found that the TB transmission in the United States was characterized by a high propensity for extensive outbreaks (k ^ = 0.09 ; 95% confidence interval = 0.09, 0.10). Conclusions: The proposed method can accurately quantify critical parameters that govern TB transmission using simple, more easily obtainable cluster data to improve our understanding of TB epidemiology.